2017
DOI: 10.3389/fphys.2017.00551
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a-5p Mediates High Glucose-Induced Endothelial Inflammation via Targeting Interleukin-1 Receptor-Associated Kinase 1 Expression

Abstract: Background and Aims: Interleukin-1 receptor-associated kinase-1 (IRAK-1) is critical for mediating toll-like receptor and interleukin-1 receptor signaling. In this study, we have examined whether IRAK-1 expression is altered in high glucose (HG)-stimulated human aortic endothelial cells (HAECs), and whether microRNAs (miRs) target IRAK-1 to regulate HG-induced endothelial inflammation.Methods: HAECs were treated with HG for 24 and 48 h. Real-time PCR, Western blot, monocyte adhesion assay, bioinformatics analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…miR‐874 can inhibit TNF‐α‐induced remodeling in human fetal airway smooth muscle cells via targeting STAT3 (Sun et al, ). In addition, miR‐874 is significantly downregulated in HG‐stimulated human aortic endothelial cells (HAEC) (Lo, Peng, & Wang, ). Here, in our studies, we verified the downregulation of miR‐874 in DN rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐874 can inhibit TNF‐α‐induced remodeling in human fetal airway smooth muscle cells via targeting STAT3 (Sun et al, ). In addition, miR‐874 is significantly downregulated in HG‐stimulated human aortic endothelial cells (HAEC) (Lo, Peng, & Wang, ). Here, in our studies, we verified the downregulation of miR‐874 in DN rats.…”
Section: Discussionmentioning
confidence: 99%
“…miR-874 can inhibit TNF-α-induced remodeling in human fetal airway smooth muscle cells via targeting STAT3 (Sun et al, 2018). In addition, miR-874 is significantly downregulated in HG-stimulated human aortic endothelial cells (HAEC) (Lo, Peng, & Wang, 2017 (Yu, Bo, Villani, Spencer, & Fu, 2016). Besides, TLR4 can link inflammation and fibrosis in chronic kidney diseases (Lepenies et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In mice with T2DM, miR-146a mimics significantly ameliorated peripheral neuropathy, principally by suppressing the expression of hyperglycemia-induced proinflammatory genes ( 50 ). Moreover, miR-146a is reportedly involved in high-glucose-induced endothelial inflammation, which suggests that it may be a novel therapeutic target for diabetic vascular disease ( 25 ). Overexpression of miR-146a inhibits osteogenesis by MSCs ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies suggested that miR-146a exerted anti-oxidative stress effect in various pathological processes in diabetic complications ( 25 27 ). Wang et al reported that miR-146a decreases high glucose induced ROS generation in endothelial cells ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…In adhesion experiments, THP-1 cells were labeled with calcein acetoxymethyl ester (Calcein-AM; Molecular Probes, Eugene, OR, USA) as previously described (Lo et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%